Sample size for the evaluation of ‘BH-65’ papaya fruits under protected cultivation - Schmildt,Edilson Romas (2019)
Abstract The cultivation of papaya under greenhouse has become recently a profitable alternative for horticultural crops in different regions of the world, among them South East Spain. The objective of this work was to determine the sample size to evaluate fruit quality features in mature fruits of ‘BH-65’ papaya cultivated under greenhouse in Almería (Spain). With this aim, fruits were harvested at stage 2 in July 2013, and at the end of the production cycle in March 2014. On each occasion and when fruits reached maturation phenological stage 5, 26 fruits were evaluated for physical characteristics (weight, length, diameter, cavity width), total soluble solids content, and color attributes of skin and pulp. The optimal sample size was calculated using a deterministic method. The physical parameters and the skin and pulp color attributes of fruits of ‘BH-65’ papaya cultivar present different experimental accuracy among themselves and between harvest seasons, requiring different sample sizes. Higher sample size is required for evaluating fruit weight. 25 fruits were necessary at harvest performed in July, but only 7 fruits in March, considering an error of 15% around the average.